The found object in textile art - Holmes, Cas (London : Batsford, 2010)
Textile artists have always used found objects, both for decoration and to imbue their work with meaning, and recently the practice has become even more popular. Cas Holmes is renowned for her use of 'the found', and her many-layered, atmospheric pieces have been shown around the world
boek
Keywords: Holmes, Cas